SEZARY SYNDROME MIMICKING GENERALIZED PSORIASIS VULGARIS - Lynoora, Eko Rianova; Rahmadewi, Rahmadewi (Institute of Topical Disease Universitas Airlangga, 2016)
Sezary syndrome is the leukemic variant of cutaneous T cell lymphoma. This disease is characterized by some reddish patches or plaques all over the skin which extends to the whole body into erythroderma, lymphadenopathy. It is also indicated by the presence of atypical lymphocytes called Sezary cells. This case report is aimed to know clinical manifestation, examination and management of Sezary syndrome which clinically resembles generalized psoriasis. A 60 years old man came with scaly reddish brown plaques almost all over his body. It was accompanied by lymphadenopathy on the supraclavicular lymph node right and left as well as intense itchy. Other clinical features were alopecia, palmoplantar hyperkeratosis, onychodysthropy, facies leonine without anesthesia on the lesion and enlargement of peripheral nerve. From a laboratory test, an increase in the number of leukocytes and, Sezary cells were found in peripheral blood smear examination; while the histopathology showed focal athrophy and acanthosis of the epidermis and dense infiltration of lymphocytes in the dermo-epidermal junction and superficial dermis. Patient received 3 x 5 mg (1 cycle) of methotrexate (MTX) with 0,1% cream mometasone furoate and 3x1 tablet of CTM for adjunctive therapy. Methotrexate was discontinued because there was a disturbance in liver function and deterioration of patient's condition. After 25 days of treatment, the patient got sepsis and then passed away. Early onset of Sezary syndrome in this case is difficult to know because the clinical manifestation is similar with psoriasis vulgaris. Supporting examination such as laboratory test, blood smears and histopathology examination could help the diagnosis. The presence of lymphadenopathy, and atypical lymphocytes in the peripheral blood and the extensive skin involvement reflect the poor prognosis. The most common cause of death was sepsis.